PERSEPSI USERS ATAS AKUNTABILITAS LAPORAN KEUANGAN PEMERINTAH DAERAH (Studi pada Pemerintah Provinsi Sulawesi Tengah) - Purnomo, Dheny (Katalogis, 2016)
This study aims to identify and analyze the perception among users (Government, Society and Supervisor) regarding financial accountability and public accountability on the financial statements of the Government of Central Sulawesi Province. Statistical test results analysis using One-way ANOVA with SPSS 17.0 shows that a) There is a difference of perception between Government, Society and Supervisor regarding financial accountability on the financial statements of the Government of Central Sulawesi province. b) There is a difference of perception between Government, Society and Supervisor regarding public accountability on the financial statements of the Government of Central Sulawesi province.